EFEKTIVITAS VARIASI KONSENTRASI FERMENTASI GULA MERAH SEBAGAI ATRAKTAN NYAMUK Aedes aegypti DI PT. X (Politeknik Kesehatan Kemenkes Bandung, 2021)
DHF is a disease caused by the virus dengue and is transmitted through the bite of the Aedes aegypti mosquito. DHF does not only occur in residential areas but also in industry. The number of breeding sites causes the mosquito population to increase. Various chemical and natural control efforts have been carried out. Mosquito resistance to chemical insecticides encourages the development of safer and environmentally friendly efforts to control dengue mosquito vectors. This effort uses mosquito traps with fermented brown sugar attractants. The purpose of this study was to determine the variation of the concentration of fermented brown sugar which was effective as an attractant for the Aedes aegypti mosquito at PT. X. This type of research is an experiment with the method Posttest Only Control Group Design. Attractant testing was carried out on 3 variations of brown sugar fermentation concentration, namely 30%, 35%, and 40%. Mosquito traps without brown sugar fermentation were used as control. The sample used in the study was mosquitoes in the area within the office. The results of data analysis using One Way Anova showed that there was a difference between the concentration of fermented brown sugar and the attractiveness of mosquitoes because the p-value was 0.031 (< 0.05). The concentration of fermented brown sugar 35% (47,2%) was the most effective for attracting mosquitoes into the trap. It is recommended that further research examines variations in the concentration of fermented brown sugar that are effective up to 100% to attract mosquitoes into the trap.